1977
DOI: 10.1507/endocrj1954.24.47
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ovulation-blocking agents upon the limbichypothalamic neuronal pathways in the rabbit brain.

Abstract: Female adult rabbits with coaxial bipolar electrodes chronically implanted in the brain were used. Evoked potentials (EVPs) were recorded in the medial basal hypothalamus (MBH) including the median eminence and the arcuate nucleus in response to stimulation of the dorsal hippocampus, medial amygdala and preoptic area. In the present experiment, the influence of ovulation-blocking drugs (pentobarbital, atropine and chlorpromazine) upon those EVPs was investigated. Since short-latency responses (less than 4.5 ms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1977
1977
1983
1983

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Data of this study are summarized in Table 1 (A, B, C). Table 1 (D) is the data of another experiment (Ishida et al, 1977), which was undertaken to estimate whether each deflection of EVPs was concerned with the direct or pauci-neuronal pathways or the multi-neuronal pathways, based on the et al (1962).…”
Section: Estrusmentioning
confidence: 99%
See 2 more Smart Citations
“…Data of this study are summarized in Table 1 (A, B, C). Table 1 (D) is the data of another experiment (Ishida et al, 1977), which was undertaken to estimate whether each deflection of EVPs was concerned with the direct or pauci-neuronal pathways or the multi-neuronal pathways, based on the et al (1962).…”
Section: Estrusmentioning
confidence: 99%
“…deflection with 1.5 to 2.5 msec peak-latency of the EVP in response to stimulation of the POA were unaffected by pentobarbital. Therefore, these responses may be mediated through the direct or the pauci-neuronal pathways (discussed in the paper of Ishida et al, 1977). Kawakami and Terasawa (1967) and reported that the amplitude of the hippocampally EVP in the periventricular arcuate nucleus decreased during estrus in the rabbit and that at the same time the amplitude of the amygdaloidly EVP increased.…”
Section: Estrusmentioning
confidence: 99%
See 1 more Smart Citation